Letter: potential selection bias in the real‐world comparison of ustekinumab versus vedolizumab as a second‐line treatment for Crohn's disease. Issue 8 (31st March 2022) - Adomi, Motohiko; Ray, Avik
LINKED CONTENT: This article is linked to Lenti et al papers. To view these articles, visit https://doi.org/10.1111/apt.16742 and https://doi.org/10.1111/apt.16896